First detection of Macrorhabdus ornithogaster in wild Eurasian Siskins (Carduelis spinus) in Germany - Legler, M.; Stelter, R.; Jung, A.; Wohlsein, P.; Kummerfeld, N. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2015)
The colonization of the gastric ascomycetous yeast Macrorhabdus (M.) ornithogaster could be associated with a chronic wasting disease in several bird species in captivity. The prevalence and clinical relevance of M. ornithogaster in wild birds is unknown in detail.In the wintering season 2012/13 injured Eurasian Siskins (Carduelis spinus, n = 8) from the area of Hannover, Lower Saxony, Germany were examined microbiologically and pathologically.In six out of eight injured Eurasian Siskins M. ornithogaster were detected. The yeast was diagnosed microscopically in wet smears from the gastric isthmus and/or in faecal samples. Histopathological examination (n = 4) of the macroscopically slightly enlarged proventriculus in infected birds demonstrated the growth of M. ornithogaster in the mucosal surface and in the ducts of the glands without an inflammatory reaction. As a possible sign of a lowered fitness, all six infected siskins had a reduced body weight (mean: 11.8 ± 1.64 g) in the lower normal weight range compared to the two injured Eurasian Siskins without M. ornithogaster (15.0 g) as well as to data from the literature. Concurrent intestinal bacterial infections comprised Escherichia coli, Clostridium perfringens or Salmonella Typhimurium, that are regarded as an abnormal bacterial flora for Eurasian Siskins.Infections with M. ornithogaster can be found in the wild population of Eurasian Siskins in Germany. The frequent occurrence of secondary bacterial infections associated with M. ornithogaster infections should be considered in the treatment and rehabilitation of finches.
Keywords: Macrorhabdus; yeast; finches; Carduelidae; dysbacteriosis; wild birds